SENSITIVITY ANALYSIS OF THE FIRST CIRCUIT OF COLD CHANNEL PIPELINE RUPTURE SIZE FOR WWER 440/270 REACTOR - Hovsepyan, A.D. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
This calculation describes an accident to analyze and study the emergency instructions in case of fracture in the airtight zone of the first circuit. Sensitivity analysis was performed to determine the extent of the fracture, when a highpressure feeder pump remains 100 N/cm2 higher than the saturation pressure in case of emergency pressure of the circuit (the pressure drop allows the main circulating pumps work). The conventional diameter of the fracture is 29 mm and the schedule of the development of events is given in the study.